Speech Acts and Implicature in Media Framing: A Pragmatic Study of Gus Miftah's 'Goblok' Controversy on Detik.com - Saragih, M Afiv Toni Suhendra (English Teaching and Linguistics Journal (ETLiJ), 2025)
This study conducts a pragmatic analysis of how Detik.com's editorial texts framed the prolonged controversy surrounding Gus Miftah's